The Correlation Between Smoking Behavior and The Use of “Used Cooking Oil” with Hypertension Incidences at Malimbu Coastal Area - I Gede Angga Adnyana; I Nyoman Bagus Aji Kresnapati; I Putu Bayu Agus Saputra; Maruni Wiwin Diarti; Yunan Jiwintarum (Jurusan Keperawatan, Poltekkes Kemenkes Mataram, 2023)
Hypertension is the main risk factor that leads to cardiovascular disease such as heart attack, heart failure and stroke, which is the highest cause of death in the world. One area with high risk of hypertension is the coastal area. The famous coastal area in the Lombok is Malimbu, located in North Lombok, West Nusa Tenggara Province. This research is an analytical observational study with a cross sectional design. This study aims to determine the correlation between smoking behavior and use of “used cooking oil” and the incidence of hypertension. Samples in this study were 70 people (n=70), and was taken using accidental sampling technique. Data were analyzed using chi-square. The results showed that the incidence of hypertension was 48% of the 70 respondents. Most of the respondents (70%), had no history of hypertension in their family. This research shows that there is no correlation between smoking behavior and the incidence of hypertension (p=0.807) with PR=1.156 (0.354 - 3.797). The use of “used cooking oil” was also found to be not correlated with the incidence of hypertension (p=0.632) with PR=1.275 (0.486 - 3.345). Although several previous studies showed that the smoking behavior and the use of used cooking oil correlate to hypertension, but this study result shows different data. This can be caused by other factors. Future research needs to examine the characteristics of smokers that may be related to the incidence of hypertension